2010
DOI: 10.1266/ggs.85.147
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the expressed MHC class II DQB gene of the Asiatic black bear, Ursus thibetanus, in Japan

Abstract: Genetic diversity estimation of the major histocompatibility complex (MHC) gene may be an important tool in the assessment of immune response ability against infectious disease. We were able to identify a near full-length expressed DQB sequence by RACE-PCR method from the Asiatic black bear, Ursus thibetanus in Japan. This is the first such full length expression in the Ursidae. The bear had at least one functional DQB locus. In phylogenetic tree analysis its DQB amino acid sequence formed a monophyletic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In this ML tree, the DQB sequences formed a clearly separated cluster from the DRB sequences, in agreement with Yasukochi et al [39]. These trees showed that the 31 sequences from the Japanese black bear formed a monophyletic group with the DQBs of the giant panda.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In this ML tree, the DQB sequences formed a clearly separated cluster from the DRB sequences, in agreement with Yasukochi et al [39]. These trees showed that the 31 sequences from the Japanese black bear formed a monophyletic group with the DQBs of the giant panda.…”
Section: Resultssupporting
confidence: 90%
“…Thus, in the present study we additionally identified 39 novel variants at the DNA level in 178 samples. The nucleotide sequence of Urth-DQB*0101 was identical to that found in exon 2 of a cDNA sequence derived from mRNA of a bear sample in our previous study [39]. This suggests the amplification of a functional DQB locus in the present study, although there is no evidence of protein translation.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations